MACHINE LEARNING-BASED ALGORITHM FOR CIRCULARITY ANALYSIS - Najmiddinov Shakhzodbek Shukhrat ugli (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. A crucial component of quality control in industrial processes is circularity analysis. It refers to the measuring of an object's roundness or circularity, which is crucial for making sure the product fits and performs as intended. Precision parts like pistons, gears, and bearings are frequently made using circularity analysis. Comparing an object's real form to its ideal circular shape is a common method for determining how circular it is. Usually, a coordinate measuring machine (CMM) or a laser scanner are used for this comparison. The circularity of the object is then ascertained by analysis of the measurement data.